(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article examines "Women’s Literature" and its emergence, the theoretical basis. The study of "Women’s Literature" in the world literature, as well as the process of its emergence, study and formation in Uzbek literature is described. The contributions of female artists to literature are illuminated by the analysis of their works.